Fodder Potential of Pearl Millet Forage Hybrids under Rainfed Conditions of Gujarat - Dhedhi, K. K.; Ansodariya, V. V.; Chaudhari, N. N.; Sanghani, J. M.; Mehta, Asha C.; Sorathiya, J. S. (International Journal of Bio-resource and Stress Management, 2023)
Field experiments were conducted during kharif, 2014, to know the performance of 29 crosses of pearl millet forage under rainfed conditions of Gujarat. Significant differences were observed among the hybrids for days to 50% flowering, days to maturity, plant height, plant population, grain yield, dry fodder yield and green fodder yield. The locations differences were found significant for all the characters except plant population and dry fodder yield. Days to 50% flowering ranged from 48 (ICMA 10999×HHVBC tall) to 65 days (check PAC 981). ICMA 07999×HHHVBC tall (181 cm) was the shortest, while, check DFMH 70 (308 cm) was the tallest hybrid. ICMA 00999×IP 6202 produced the maximum dry fodder yield (138 q ha-1) among all the crosses followed by ICMA 01888×ICMV 05222 (129 q ha-1) and check ICMV 08111 (119 q ha-1). The cross ICMA 00999×IP 6202 produced the highest green fodder yield (262 q ha-1) among all the crosses followed by ICMA 01888×ICMV 05222 (250 q ha-1) and check ICMV 08111 (233 q ha-1). The hybrids ICMA 00999×IP 6202 and ICMA 01888×ICMV 05222 recorded high green fodder yield, dry fodder yield and plant height than the best check ICMV 08111. Thus, these two hybrids may be considered for general cultivation under rain fed conditions of Gujarat.